Targeting Mechanisms for Problematic Pornography Use Interventions. - Todorovic, Luka; Huisman, Mark; Ostafin, B. D. (Sexual Health & Compulsivity)
Evidence-based treatments for problematic pornography use (PPU) are missing, so users seek help through online communities formed around their concerns. This study investigated the effectiveness of brief interventions in (I) reducing desire for pornography use and (II) increasing self-efficacy regarding pornography use, in a non-clinical online sample (n = 711). Participants' craving for pornography was activated and then they were randomly assigned to one of the intervention conditions: life meaning, willpower, mindfulness, awe, or active control. The results indicated that life meaning could be effective in reducing craving for pornography. Future research should investigate the potential of similar interventions with clinical samples.